1997
DOI: 10.1074/jbc.272.31.19111
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Expression of a Human Kidney Na+:HCO3−Cotransporter

Abstract: Several modes of HCO 3؊ transport occur in the kidney, including Na ؉ -independent Cl/HCO ؊ and sensitivity to inhibition by 4,4-diisothiocyanatostilbene-2,2-disulfonic acid) suggested a strategy for cloning the other transporters based on structural similarity with the AE family. An expressed sequence tag encoding part of a protein that is related to the known anion exchangers was identified in the GenBank™ expressed sequence tag data base and used to design an oligonucleotide probe. This probe was used to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
153
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 22 publications
1
153
1
2
Order By: Relevance
“…Oocyte Experiments: hkNBCe1 and S427L cDNAs-The hkNBCe1 cDNA was generated by RT-PCR using oligo(dT)-primed human kidney poly(A) ϩ RNA (Clontech) and primers corresponding to the start and stop of the known sequence (19): F10 (5Ј-ATgTCCACTgAAAATgTggAAgggAAgCCC), R10 (5Ј-TTATCAgCATgATgTgTggCgTTC).…”
Section: Methodsmentioning
confidence: 99%
“…Oocyte Experiments: hkNBCe1 and S427L cDNAs-The hkNBCe1 cDNA was generated by RT-PCR using oligo(dT)-primed human kidney poly(A) ϩ RNA (Clontech) and primers corresponding to the start and stop of the known sequence (19): F10 (5Ј-ATgTCCACTgAAAATgTggAAgggAAgCCC), R10 (5Ј-TTATCAgCATgATgTgTggCgTTC).…”
Section: Methodsmentioning
confidence: 99%
“…Expression in HEK293 cells demonstrated that Pendrin can function as a Cl Ϫ /OH Ϫ , Cl Ϫ / HCO 3 Ϫ , and Cl Ϫ /formate exchanger (16). Sodium/bicarbonate co-transporters have been characterized in the kidney (56,57). Sequence alignment of the extreme carboxyl-terminal tail of bicarbonate transport proteins (Fig.…”
Section: Figmentioning
confidence: 99%
“…These findings indicate that NBC1 has essential roles not only in whole-body acid-base balance but also in the maintenance of homeostasis in several tissues. There are two major splicing variants of NBC1, pancreastype NBC1 (pNBC1) (9) and kidney-type NBC1 (kNBC1) (10)(11)(12). pNBC1 and kNBC1 are 93% identical, but the N-terminal 85 aa of pNBC1 are replaced by 41 different amino acids in kNBC1.…”
mentioning
confidence: 99%